OPTIMIZING THE FULFILLMENT OF TODDLER NUTRITION THROUGH EMPOWERING CADRES AND MOTHERS OF TODDLERS WITH EDUZITA ACTIVITIES - Dwi Yuliawati; Ari Kusmiwiyati (Universitas Airlangga, 2025)
Humans need nutrition to optimize growth and development. A good understanding of how to feed babies and children is very important because babies and children are the next generation for the future of the nation. Therefore, it is necessary to intervene to increase parental knowledge through Toddler Nutrition Education (EDUZITA) activities carried out to empower the community, especially cadres and mothers of toddlers in optimizing toddler growth. This community empowerment activity was carried out through cadre mentoring activities on May 11, 2024 and toddler mother class activities on May 18, 2024. The empowerment model used is Unlimited Totality Health Empowerment (UTHE) with several types of activity models carried out, namely lectures, group discussions, video screenings, and demonstrations. This community empowerment is proven to increase the knowledge of cadres about toddler nutrition as shown by the results of the pre-test and post test with a good category that has increased from 40% to 90%. Similarly, the knowledge of mothers of toddlers in the good category showed an increase before and after counseling by 20% to 93.3%. In addition, the success of the activity is also indicated by the ability of cadres to educate the preparation of the toddler menu correctly using the “Fill My Plate” media. EDUZITA activities can be a means of sharing knowledge and active discussion between the service team and activity participants on various maternal and child health problems.